Comparing the effectiveness of teaching study methods and time management on academic self-efficacy and academic selfregulation and biology course performance of 12th grade experimental sciences male and female students - Saman Azari, Jafar; Livarjani, Sholeh; Azmoodeh, Masoumeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The present research was done with the aim to compare the effectiveness of study methods and time management training, on the academic self-Efficacy, academic self-regulation and performance in biology course of female and male students of twelfth grade in experimental science major. Methods: The research method was quasi-experimental with a pretest and posttest design in addition to the control group. The statistical society consisted of all female and male students in twelfth grade of experimental sciences major in Tabriz city during 2021-2022; among them 52 students were selected in one step cluster sampling method as the sample case and categorized in two groups of experimental group (26 students) and the control group (26 students). In order to estimate students’ academic self-efficacy, the standard questionnaire of Jinks and Morgan (1999) was applied. Savari and Arabzadeh (2013) questionnaire was used to analyze their academic self-regulation; and to evaluate students’ performance, their current and previous academic year’s final scores in biology course was utilized. The validity of research instruments was confirmed by the approval of specialists and the reliability was estimated and approved by calculating Cronbach alpha coefficient (α> 0.7). Prior to the study, pre-test of academic self-efficacy and academic self-regulation was implemented in both groups. The experimental group had received study methods and time management trainings through a package in 8 sessions with 60 minutes training, but the control group had not received any training therapy. After the training course in the post-test stage, both of the groups answered to the research instruments of the pre-test stage. Students’ final scores in biology lesson of previous and current academic year was also gained. The research data was analyzed with analysis of covariance using SPSS. Results: Based on the obtained results, the study methods and time management training had the same effectiveness on female and male students’ academic self-efficacy, academic self-regulation and performance in biology course. Conclusion: According to the results of the research, critical thinking and social cognitive training has increased the emotional readiness of female students in the first year of high school. Critical thinking training created a significant difference between the control and experimental groups in terms of the variable of emotional creativity. Also, critical thinking and social cognitive training has improved innovation in female students of the first year of high school. Teaching critical thinking and social cognition has not had a significant impact on students.